Pengaruh Komunikasi Interpersonal pada Kinerja Organisasi : Sebuah Meta-Analisis - Rahmi Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research investigates the significant impact of interpersonal communication on overall organizational performance. This type of research is meta-analysis research. Inclusion criteria in research are research from national or international journals indexed by SINTA and Scopus, research related to personal communication on organizational performance, research published in 2020-2024, and attaching complete data in analyzing the effect size value. This analysis includes a comprehensive review of the existing literature on this topic, spanning various industries and organizational settings. The meta-analysis results show a strong positive influence between interpersonal communication and organizational performance with a value of rES=0.818; z= 0.629; p < 0.001) with a high effect size category. Furthermore, this research reveals that effective interpersonal communication can increase team member engagement, improve collaboration, and improve problem-solving skills, ultimately leading to better organizational outcomes. In conclusion, there is a positive influence between personal communication on organizational performance Keywords: Interpersonal Communication, Meta-analysis, Organizational performance